The Apocalypse in the early Middle Ages - Palmer, James T. (James Trevor) (Cambridge : Cambridge University Press, 2014)
This groundbreaking study reveals the distinctive impact of apocalyptic ideas about time, evil and power on church and society in the Latin West, c.400-c.1050. Drawing on evidence from late antiquity, the Frankish kingdoms, Anglo-Saxon England, Spain and Byzantium and sociological models, James Palmer shows that apocalyptic thought was a more powerful part of mainstream political ideologies and religious reform than many historians believe. Moving beyond the standard'Terrors of the Year 1000', The Apocalypse in the Early Middle Ages opens up broader perspectives on heresy, the Antichrist and Last World Emperor legends, chronography, and the relationship between eschatology and apocalypticism. In the process, it offers reassessments of the worlds of Augustine, Gregory of Tours, Bede, Charlemagne and the Ottonians, providing a wide-ranging and up-to-date survey of medieval apocalyptic thought. This is the first full-length English-language treatment of a fundamental and controversial part of medieval religion and society.
How the world ends -- The end of civilisation (c. AD 380-c. AD 575) -- The new urgency (c. AD 550 -c. AD 604) -- The ends of time and space (c. AD 600-c. AD 735) -- Pseudo-Methodius and the problem of evil (c. AD 680-c. AD 800) -- Charlemagne, Pater Europae (c. AD 750-c. 820) -- A golden age in danger (c. AD 820-c. AD 911) -- The year 1000 and other Apocalypticisms (c. AD 400-c. AD 1033) -- The end (c. AD 400-c. AD 1033).
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: End of the world -- History of doctrines -- Middle Ages, 600-1500.; End of the world -- History of doctrines -- Early church, ca. 30-600.; Civilization, Medieval